Populism: a deflationary view. Issue 1 (2nd January 2017) - Molyneux, Maxine; Osborne, Thomas
Abstract: This paper takes a critical, synoptic view of the current upsurge of populism. Populism, it is argued, has long been a feature of liberal democracies in so far as claims are made for democracy to be as directly expressive as possible of the will of its subjects. Yet populisms are hybrid in form and parasitic on existing political arrangements. What unites them is more to do with what they oppose than what they espouse. Above all, it is the norms of liberalism that are brought into question by populist proponents of direct democracy with their characteristic hostility towards elites, experts and the so-called establishment. In so far as all populisms can be dangerous this lies in the degree to which they oppose the existing norms of liberalism and seek to undermine its moderating institutions. Rather than relying on generic theories of populism to explain contemporary developments, what needs investigation is the degree to which particular populisms prioritize fear over judgement, unqualified assertion over reasoned deliberation and resentment over the moderation of power.